Wolfgang Tillmans : to look without fear - Lowry, Glenn D.; Chéroux, Clément; Onabanjo, Oluremi C.; Kuo, Michelle Y.; Museum of Modern Art (New York, N.Y.); Art Gallery of Ontario; San Francisco Museum of Modern Art (New York : The Museum of Modern Art, 2022)
"A visionary creator and intrepid polymath, Wolfgang Tillmans unites formal inventiveness with an ethical orientation that attends to the most pressing issues of life today. While his work transcends the bounds of any single artistic discipline, he is best known for his wide-ranging photographic output. From trenchant documents of social movements to windowsill still lifes, sensitive portraits to architectural studies, ecstatic images of nightlife to cameraless abstractions, astronomical observations to intimate nudes, he has explored seemingly every genre of photography imaginable, continually experimenting with ways to make new pictures and deepen the viewer's experience. Published in conjunction with a major exhibition of Tillmans's work at the Museum of Modern Art, this copiously illustrated volume surveys four decades of the artist's career. An outstanding group of writers offer diverse essays addressing key aspects of his multifaceted practice, and a new text by Tillmans himself elucidates the distinctive methodology behind his system of presenting photographs."--
Organized by Roxana Marcoci.
"Wolfgang Tillmans: To Look without Fear" : September 12, 2022-January 1, 2023, Museum of Modern Art, New York, New York, United States.
"Wolfgang Tillmans: To Look without Fear" : Spring-Fall 2023, Art Gallery of Ontario, Canada.
"Wolfgang Tillmans: To Look without Fear" : Fall 2023-Spring 2024, San Francisco Museum of Modern Art, San Francisco, California, United States.
kunstcatalogus
Keywords: Photography, Artistic -- 20th century -- Exhibitions; Photography, Artistic -- 21st century -- Exhibitions; Tillmans, Wolfgang; Tillmans, Wolfgang; Livres de photographies